ANALYSIS OF COFFEE CONSUMER BEHAVIOR IN JEMBER AND ITS IMPLICATIONS TO DEVELOPMENT STRATEGY OF LOCAL COFFEE AGROINDUSTRY - Trias Primadani; joni Murti Mulyo Aji; M Sunarsih (UPT Penerbitan Universitas Jember, 2012)
This research is aimed to identify: (1) consumer perception towards the local ground coffee (powder) products; (2) factors affecting consumer decision to purchase coffee; (3) characteristics of coffee powder sought by consumers; and (4) right product development strategy for the local coffee. Study area is determined by deliberately (purposive method). Analyses of the data used are analytical hierarchy process (AHP) and factor analysis. The results show: (1) the respondents perceived that “Kapal Api” coffee is better than the local coffee and other branded coffee, (2) availability and product, price and social environment factors, and product quality are identified as the factors affecting consumer decision to purchase coffee in Jember, (3) Based on priority scales, characteristics of coffee powder sought by consumers are price (St2), product (St1),promotion (St4), and place (St3) respectively, (4) Based on the perceptions of respondents in details, product strategy consists of the taste (P5), aroma (P6), brand (P4), practicality (P1), packaging design (P3), package size (P2), meanwhile promotion strategies consists of advertisement (P7), sales promotion (P8), public relations (P10), and face to face sales (P9).